Health care utilization patterns of patients enrolled in an interdisciplinary program for back pain - Sara Davin, Psy.D., MPH; Brittany Lapin, PhD., MPH; Belinda Udeh, PhD; Sarah Rispinto, PhD; Nicolas R. Thompson, MS; Ryan Honomichl, PhD; Andre Machado, MD; Irene L. Katzan, MD (North American Spine Society Journal)
Background: Chronic low back pain is a costly condition and the leading cause of disability worldwide. A recent call to action identified the overuse of low-value health care as ineffective and potentially harmful in the context of back pain. Interdisciplinary pain programs (IPPs) incorporate physical therapy and behavioral pain treatments with the goal of empowering patients to actively use skills to self-manage pain, decreasing stress, disability, and reliance on low-value care. While IPPs are deemed “cost-effective,” few studies elaborate upon the patterns of healthcare utilizations among patients who complete IPPs with attention to valued-based care. The aim of this study was to describe healthcare patterns of patients participating in a interdisciplinary pain program (IPP) for chronic low back pain. Methods: This observational cohort study describes the healthcare utilization of a group of adult patients (N=143) who participated in an IPP for chronic back pain compared to patients who did not complete the entire program (N=112), and those who were eligible for the program but chose not to participate (N=76). Patterns of healthcare utilization were evaluated in a 12-month period before and after IPP participation. Healthcare utilization categories included outpatient resources, specialist visits, imaging, pain interventional procedures, and acute care utilization. Opioid use was also extracted based on inpatient and outpatient orders, as well as days on opioids within 2 weeks following an emergency department visit or hospitalization. Utilization was defined as a health care visit in which the primary or secondary diagnosis or procedure reason was back pain related. Relative value units (RVUs) measure value used in Medicare reimbursement for physician services. Results: Overall, healthcare utilization was not markedly different in the 12 months before and after IPP across the 3 groups (graduates, drop-outs, or no participation). However, sub-grouping analyses revealed significant reductions in opioid prescriptions, x-rays, and ED visits in the IPP group for the 12 months after the program, as well as an increased utilization of behavioral pain management. Conclusions: Adult patients who participated in an IPP for chronic low back pain demonstrated significant reductions in utilization in opioid prescriptions, x-rays and ED visits, while also showing increased participation in active therapies such as behavioral pain management. These findings suggest that participation in a IPP could influence future value-based healthcare decisions, in turn also influencing cost.